The Effect of Celebrity-Product Congruence on Purchase Intention with Source Credibility and Para Social Relationship - Umi Maisyaroh; Soepatini (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
Online shopping has become a new culture along with the growth of startups in the world of online shopping, this culture is increasingly growing and developing among people who increasingly want convenience and sophistication in their lives. The purpose of this research is to analyze the influence of Celebrity-Product Congruence on Purchase Intention with Source Credibility and Parasocial Relationship as Intervening Variables on Tiktok Live Streaming. This type of research is quantitative research. The population in this study is the entire community who use the Tiktok application and who know Fujianti Utami. This research uses primary data. The total sample for this research was 189 respondents. Sampling technique in this research. using purposive sampling. This research uses SMARTPLS 3.0 software. This research uses Structural Equation Model (SEM) analysis with Partial Least Square (PLS). The results of this research are that source credibility has a positive influence on purchase intention. Source credibility has a positive influence on parasocial relationships. Parasocial relationship mediates the relationship between source credibility and purchase intention. Parasocial relationships have a positive influence on purchase intention. Celebrity product congruence has a positive influence on source credibility. Source credibility mediates the relationship between celebrity product congruence and purchase intention. Source credibility mediates the relationship between celebrity product congruence and parasocial relationships. Source credibility and parasocial relationship mediate the relationship between celebrity product congruence and purchase intention.